Akibat Hukum Penolakan Pengajuan Peninjauan Kembali Terhadap Pelaksanaan Eksekusi Pidana Mati Terpidana Pelaku Tindak Pidana Narkotika - Fajri Almanar (Sebelas Maret University, 2019)
This research aims to determine the legal consequences of rejection of the submission of the Judicial Review sentenced to death of Narcotics Criminal (Study of Supreme Court Decision Number 145 PK /PID.SUS / 2016) and the appropriateness of reasoning based on Article 263 jo. Article 268 of the Criminal Procedure Code. This research is a normative legal research that is prescriptive. The approach used isthe approach of law (statue approach). Research resources in the form of primary legal materials and secondary legal materials. Techniques of collecting legal materials through document studies (library research) with techniques of legal material analysis based on the method of syllogism through deductive thinking patterns. Based on the result of the research, the reason for the submission of the Judicial Review sentenced to death of Fredi Budiman that is new evidence, a mistake of the Judge, and contradictory decisions is not in accordance with Article 263 jo. Article 268 of the Criminal Procedure Code based on the Judges Consideration, then another issue concerning the legal consequences arising from the rejection of the review is the execution of a death which has been in accordance with Article 270 jo. 271 that the execution is carried out by the Prosecutor and its implementation is not done in public and according to the Act.Keywords: Judicial Review, Legal Consequences, Death Penalty, Narcotics.